Compound heterozygosity for a frameshift mutation and an upstream deletion that reduces expression of SERPINH1 in siblings with a moderate form of osteogenesis imperfecta. Issue 8 (9th June 2019) - Schwarze, Ulrike; Cundy, Tim; Liu, Yajuan J.; Hofman, Paul L.; Byers, Peter H.
Abstract: SERPINH1 encodes the collagen chaperone HSP47 that binds to arginine‐rich sequences in the type I procollagen trimers and provides the final steps in the folding and stabilization of the triple helical domain. Loss of both alleles in mice results in very early embryonic lethality. SERPINH1 mutations have been associated with one of the rarest forms of recessively inherited osteogenesis imperfecta (OI) with a moderate to severe phenotype. We identified a family with non‐consanguineous unaffected parents who had two children with moderate short stature, low bone density, and fractures. Both children were compound heterozygotes for two mutations: a frameshift in the last exon that deleted the RER retention signal, and a 5, 274 bp deletion 2.37 kb upstream from the transcription start site. The maternally‐inherited frameshift allele was expressed at normal levels, but the protein was unstable. The mRNA encoded by the second allele represented about 50% of that from the frameshift‐containing allele. The upstream deletion was inherited from the father, and the mRNA encoded by that allele in his cultured dermal fibroblasts was also expressed at a low level, which confirmed that this domain had a regulatory function for SERPINH1 . Regulatory mutations are uncommon causes of human genetic disorders, and the ability to measure expression levels in appropriate cells is key to their identification.